Situation and Professional Development Needs of Foreign Teachers in Thailand - Srisitanont Luangkrajang, Manita (Journal of Liberal Arts Prince of Songkla University, 2023)
The objectives of this research are to 1) investigate the situation of foreign teachers in Thai educational settings; 2) survey their needs for professional development; and 3) propose solutions to overcome the obstacles they faced based on the collected data. The subjects of this study were 13 foreign teachers in a demonstration school in the central region of Thailand. The research tool utilized for the purpose of this study was a semi-structured interview where foreign teachers were asked to reflect on their teaching performance and investigate their needs for professional development. The demographic information, answers from the checklist and the survey were presented in a descriptive analysis. A content analysis was applied to identify and interpret the data gained from the interview, with conclusions drawn from a directed content analysis of the situation and needs of professional development. The findings revealed that their performance in the classroom was effective despite administrative policies of the school, language barriers and the issue of cultural differences posing major challenges to them. The areas that should be included in the professional development program are those that had impacts on their performance in the classroom such as instructional design, classroom management, and contents in the main subject. In order to make the professional development program effective and engaging for the foreign teachers, their opinions should be considered. They should be able to propose the topic or the activities related to their professional development that would correlate to their needs and interests.